Summarizing as a Strategy for Science Text Comprehension: Text-Based Versus Content-Based Processing. Issue 8 (17th November 2019) - Leopold, Claudia; Brückner, Annette; Dutke, Stephan
ABSTRACT: In this experiment, we contrasted two instructions in which the focus of summary writing was varied. We predicted that students would better understand a scientific text when they learn to focus their summaries on the referential content rather than on the hierarchical structure of the text. In a 2 × 2 factorial experiment, 85 Grade-10 students were instructed (a) to focus the text's referential content or the text's hierarchical structure, and (b) received drawings depicting parts of the text's content or received the text without drawings. After reading the text, the participants summarized the text and were tested for their learning performance. Instructing participants to focus on the referential content affected the structure of their summaries and led to a better understanding than focusing on the hierarchical structure of the text. Summary quality indicators mediated the effect of the summary training on comprehension performance.